Pengaruh Dukungan Akademik Dan Faktor Sikap Terhadap Keinginan Berwirausaha Bidang Teknologi (Technopreneur) Pada Mahasiswa - Ganjar Ndaru Ikhtiagung; Soedihono Soedihono (JURNAL ILMIAH MANAJEMEN & BISNIS, 2018)
This study explain Academic Support with production base education method or vocational which is applied in Polytechnic State Of Cilacap (PNC) to Influence Factor Attitude that will ultimately increase student interest to plunge in the world of technopreneur. The sample used is 170 students majoring in technology field. Determination of sample using purposive sampling with technique of path analysis and test sobel. The result of the first hypothesis shows the pattern of vocational learning applied in PNC as Academic Support does not support student entrepreneurship interest, the second hypothesis shows the role of Academic Support in the PNC environment has a significant impact on the increase of student attitudes in the effort to influence entrepreneurship interest, and the third hypothesis shows that attitude Factors influence the interest of students to entrepreneurship. The mediation test of attitude factor variables acts to mediate between the variables of Academic Support on the entrepreneurial intention variables in technology (technopreneur).